Evaluation of the Family Based Love for Literacy (CLBK) Program as an Initiative to Increase Visits to the Ampenan Tengah Urban Village Library, Mataram City - Nurwahyuningsih Nurwahyuningsih; Siti Atika Rahmi; Amin Saleh (The Future of Education Journal, 2026)
The Family-Based Literacy Love Program (CLBK) is an innovative service developed by the Ampenan Tengah Village Library in Mataram City to promote a culture of literacy and increase community visits to the library through active family involvement. This study aims to evaluate the implementation of the CLBK Program using the CIPP (Context, Input, Process, Product) evaluation model. The research employed a qualitative approach with an evaluative method. Data were collected through observations, interviews, and documentation, and analyzed using an interactive data analysis technique. The findings indicate that the CLBK Program has objectives that align with community needs and has contributed to improving reading interest, family engagement, and library visitation. However, the program has not yet been implemented optimally due to several challenges, including low community participation, limited managerial capacity in program development, inadequate facilities and infrastructure, and budget constraints. Therefore, strengthening the capacity of program managers, improving library facilities, and ensuring sustainable financial support are essential to enhance the long-term implementation and effectiveness of the CLBK Program for the community.